Globalisation and Indian federalism - Tremblay, Reeta C. (2001)
A number of centripetal and centrifugal forces have been at work in support and against Indian federal structure since Independence. The author of this article sees challenge of a different kind in some recent trends, mainly from globalisation. The inherent perils, according to her, lie in the decline of the sovereignty of the nation-state and a diminishing political power. Several options like political empowerment and administrative decentralisation at grassroots level, development of civil society organisations, efforts to reduce regional disparities and an enhanced role for the national government, have been suggested to absorb the impact of globalisation. - Reproduced
Keywords: Globalization - India; Federalism - India; Federalism